(untitled) (Journal of Bangladesh Institute of Planners, 2011)
This paper articulates the measurement of the degree of spatial agglomeration and the identification of thana wise location patterns of Dhaka Metropolitan Development plan (DMDP) in respect to slums and industries. It develops a[ understanding of spatial agglomeration of slums among geographic spaces due to spatial convergence of industrial investment. The study has been conducted through calculating the weight matrix, Moran’s 1 values and spatial auto regressive model to develop the present scenario of spatial auto-correlation in Dhaka city. The spatial econometric analysis reveals that spatial dependence between slum agglomeration and industrial concentration exists and ignoring this spatial dependency in policy making would mislead the capital investment for future. Journal of Bangladesh Institute of Planners Vol. 4, Dec 2011, pp. 1-13